Higher prices, higher quality? Evidence from German nursing homes - Annika Herr; Hanna Hottenrott (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Objectives: This study investigates the relationship between prices and quality of 7,400 German nursing homes controlling for income, nursing home density, demographics, labour market characteristics, and infrastructure at the regional level. Method: We use a cross section of public quality reports for all German nursing homes, which had been evaluated between 2010 and 2013 by external institutions. Our analysis is based on multivariate regressions in a two stage least squares framework, where we instrument prices to explain their effect on quality. Results: Descriptive analysis shows that prices and quality do not only vary across nursing homes, but also across counties and federal states and that quality and prices correlate positively. Second, the econometric analysis, which accounts for the endogenous relation between negotiated price and reported quality, shows that quality indeed positively depends on prices. In addition, more places in nursing homes per people in need are correlated with both lower prices and higher quality. Finally, unobserved factors at the federal state level explain some of the variation of reported quality across nursing homes. Conclusion: Our results suggest that higher prices increase quality. Furthermore, since reported quality and prices vary substantially across federal states, we conclude that the quality and prices of longtermcare facilities may well be compared within federal states but not across.
Keywords: I11; L11; L15; I18; 330; nursing homes; care quality; price; long-term care; two-stage least squares